The Erlangen Questionnaire: a new 5-item screening tool for obstructive sleep apnea in a sleep clinic population - A prospective, double blinded study - Traxdorf, Maximilian; Tziridis, Konstantin; Scherl, C.; Iro, Heinrich; Haferkamp, Jens (European Review for Medical and Pharmacological Sciences, 2017)
OBJECTIVE: The aim of this study was to develop and validate a simplified screening tool for identifying obstructive sleep apnea (OSA) in a sleep clinic population. PATIENTS AND METHODS: A total of 160 patients from a sleep clinic population was enrolled in the prospective, double-blinded study. OSA was defined by using diagnostic criteria of the ICSD-3 after overnight polysomnography (n=96) or polygraphy (n=64). The first 60 patients filled out a multi-item questionnaire and formed the development group. Subsequently, the five most predictive factors were selected to create the Erlangen Questionnaire (EQ). For validation of the EQ, the next 100 patients formed the validation group. RESULTS: The following factors were incorporated into the 5-item EQ: (1) ESS > 10, (2) age > 60, (3) gasping and (4) cardiovascular risk factors, (5) witnessed apneas. The EQ had sensitivities of 94.3%, 92.7% and 92.3%, specificities of 50.0%, 33.3% and 22.9%, positive predictive values of 81.5%, 62.9% and 29.6%, and negative predictive values of 78.9%, 78.9% and 89.5% with respect to mild, moderate and severe OSA. CONCLUSIONS: EQ is a compact 5-item-based, concise and easy-to-use screening tool to identify both male and female patients with OSA in a sleep clinic-population and exhibits all essential factors of internal and external validity. The results of the EQ are comparable to the best-validated and most commonly used STOP-Bang questionnaire regarding sensitivity and specificity in a sleep clinic population.
EVALuna2:33218